Waterproof mortar containing modified basalt fibers as well as preparation method and application of waterproof mortar

By forming a polymer interface layer on the surface of the basalt fiber and bonding to silica, the bonding strength between the basalt fiber and cement is improved, the problem of insufficient interface bonding strength in the prior art is solved, and efficient waterproofing is achieved Mortar performance is improved.

CN119430813APending Publication Date: 2025-02-14GUANGDONG LONGHU SCI & TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411825245.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, the interface bonding strength between basalt fibers and cement-based materials is poor, which affects the application of basalt fibers in cement-based materials. The existing modification methods are complex, costly and unsatisfactory.

Method used

Through polymer emulsion, silicone emulsion and coupling agent, a polymer interface layer is formed on the surface, combined with silica powder to bond during drying to form modified basalt fibers, improving its adhesion to cement Knot force.

Benefits of technology

The modified basalt fibers form a three-dimensional network structure in the waterproof mortar, which improves the bonding strength, crack resistance and waterproof performance, and is simple in preparation and relatively low in cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005184080320000111
    Figure BDA0005184080320000111
Patent Text Reader

Abstract

The invention belongs to the technical field of waterproof mortar, and particularly relates to waterproof mortar containing modified basalt fibers as well as a preparation method and application of the waterproof mortar. The waterproof mortar containing the modified basalt fibers is prepared from the following components in parts by weight: 35 to 40 parts of cement, 55.3 to 62.4 parts of aggregate, 1 to 2 parts of the modified basalt fibers, 1 to 1.5 parts of redispersible latex powder, 0.1 to 0.2 part of cellulose ether, 0.1 to 0.2 part of a de-foaming agent, 0.1 to 0.2 part of a water reducing agent and 0.3 to 0.6 part of a water repellent. The waterproof mortar disclosed by the invention is high in bonding strength, good in freeze thawing resistance, high in cracking resistance, low in shrinkage rate and water absorption rate and excellent in comprehensive performance, and has a wide market prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of waterproof mortar, and specifically relates to a waterproof mortar containing modified basalt fiber, and a preparation method and application thereof. Background Art

[0002] Cement mortar is a building material made of cement, fine aggregate, water and additives. It is widely used in the construction industry, mainly for masonry, plastering, ground leveling, waterproofing, etc. As a basic and important building material, the performance of cement mortar directly affects the quality and service life of the construction project. Subway tunnel engineering refers to the construction of underground passages and their ancillary facilities for subway trains. Subway tunnel engineering is an important part of the construction of urban rail transit systems. It not only requires a high level of engineering technology, but also needs to consider safety, environmental protection, economic and social impacts and other factors.

[0003] The requirements for waterproof mortar in subway tunnel projects are very strict, which is mainly determined by the special use environment and functional requirements of subway tunnels: 1. The structure of subway tunnels is usually made of concrete or reinforced concrete, and waterproof mortar needs to form a strong bond with these substrates. When subway trains are running, vibrations and dynamic loads will be generated, which puts higher requirements on the bonding performance of the waterproof layer. 2. Although most of the subway tunnels are located underground, the temperature changes inside and outside the tunnels are still significant in cold areas or places with large seasonal temperature differences. Especially in winter, the outside of the tunnel may be cold or even frozen, while the inside is relatively warm. Waterproof mortar needs to have good freeze-thaw resistance to prevent material damage caused by temperature changes. 3. During the construction and operation of subway tunnels, certain settlement, shrinkage or other forms of structural deformation may occur. 4. If the shrinkage rate of waterproof mortar is too high during the hardening process, it is easy to cause hollowing, cracking and other problems, affecting the waterproof effect. 5. Subway tunnels are in a humid environment for a long time, and groundwater and seepage are common problems. Waterproof mortar with low water absorption can effectively block moisture penetration, prevent moisture inside the tunnel, and protect the structure from water erosion. 6. The structure of subway tunnels usually contains a large number of steel bars. The infiltration of water will accelerate the corrosion of the steel bars and affect the safety of the structure. Waterproof mortar can effectively isolate moisture and protect the steel bars from corrosion through its low water absorption and good waterproof performance.

[0004] Basalt fiber is made by melting basalt ore at high temperature and drawing it. It has silicates similar to natural ore. my country has listed basalt fiber as one of the four major fibers (carbon fiber, aramid, ultra-high molecular weight polyethylene, basalt fiber) for key development and has achieved industrial production. Basalt fiber is a new type of inorganic environmentally friendly green high-performance fiber material. Due to the smooth surface and low surface energy of basalt fiber, the interfacial bonding strength between basalt fiber and cement-based materials is poor, which affects the application of basalt fiber in cement-based materials. The commonly used methods for improving basalt in the prior art are: (1) by modifying the surface of basalt fiber to have cations, the surface potential of the carrier is increased, the surface of the carrier is positively charged, and the electrostatic attraction is used to promote the fixation of microorganisms, which is beneficial to the immobilization of microorganisms; (2) the surface of basalt fiber contains active functional groups after modification, which increases the surface energy of the carrier. The hydroxyl, carbonyl or carboxyl groups contained in the modified basalt fiber have a positive effect on the adhesion and growth of microorganisms on the surface of the carrier. However, the above-mentioned modification methods are complicated and costly, and the comprehensive effect of application in cement mortar is not ideal.

[0005] Therefore, there is an urgent need for a waterproof mortar containing modified basalt fiber and a preparation method and application thereof. Summary of the invention

[0006] The purpose of the present invention is to provide a waterproof mortar containing modified basalt fiber and a preparation method and application thereof.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A waterproof mortar containing modified basalt fiber, comprising the following components in parts by weight: 35-40 parts of cement, 55.3-62.4 parts of aggregate, 1-2 parts of modified basalt fiber, 1-1.5 parts of redispersible latex powder, 0.1-0.2 parts of cellulose ether, 0.1-0.2 parts of defoamer, 0.1-0.2 parts of water reducing agent and 0.3-0.6 parts of water repellent;

[0009] The preparation method of the modified basalt fiber comprises the following steps: by weight:

[0010] (1) mixing 3-8 parts of a coupling agent, 15-25 parts of a polymer emulsion, 3-5 parts of an organosilicon emulsion and 62-79 parts of water, and stirring until uniform to obtain a modified liquid;

[0011] (2) adding basalt fiber into the modified liquid and soaking for 1-2 hours to obtain a mixed material;

[0012] (3) The mixed material is placed in a suspension dryer, and then silicon dioxide is added and dried to obtain modified basalt fiber.

[0013] Furthermore, in the step (2), the weight ratio of the basalt fiber to the modified liquid is 1:

[0014] (1-2).

[0015] Furthermore, in the step (3), the weight ratio of basalt fiber to silicon dioxide is (3-4):1.

[0016] Furthermore, the coupling agent in step (1) is one or both of a silane coupling agent and a phthalate coupling agent.

[0017] Furthermore, in step (1), the polymer emulsion is selected from one or more of pure acrylic emulsion, styrene acrylic emulsion, acetic acid acrylic emulsion, silicone acrylic emulsion and chloroacrylic emulsion.

[0018] Furthermore, the polymer emulsion comprises styrene acrylic emulsion, silicone acrylic emulsion and pure acrylic emulsion in a weight ratio of 1:(1.3-1.5):(0.4-0.6).

[0019] Styrene acrylic emulsion, purchased from Badfu Group Co., Ltd., model RS300L. Silicone acrylic emulsion, purchased from Shanghai Baolijia Chemical Co., Ltd., model BLJ-KD96. Pure acrylic emulsion, purchased from Badfu Group Co., Ltd., model RS2608.

[0020] Furthermore, the glass transition temperature of the polymer emulsion is greater than 15° C. If the glass transition temperature is too low, the fibers are easily adhered, which is not conducive to dispersion.

[0021] Furthermore, the organosilicon emulsion is one or both of silane emulsion and siloxane emulsion.

[0022] Furthermore, the average particle size of the silicon dioxide is 10 nm and the average specific surface area is 380 m 2 / g. Purchased from Jinlei Technology, model JL-SiO2-N10.

[0023] Adding the modified basalt fiber prepared by the above method to the waterproof mortar of the present invention can improve the bonding strength of the waterproof mortar under different conditions. The present invention infiltrates the interior of the basalt through polymer emulsion, silicone emulsion and coupling agent, and forms a polymer interface layer on the surface, and adds silicon dioxide powder during the drying process. The polymer emulsion, silicone emulsion and interface agent are bonded with silicon dioxide on the surface of the basalt fiber to form a rough surface, thereby increasing the bonding force with cement when used in the waterproof mortar later; the modified basalt fiber forms a three-dimensional network structure inside the waterproof mortar, thereby increasing the softness and crack resistance of the waterproof mortar, and at the same time improving the waterproof performance of the waterproof mortar.

[0024] Furthermore, the redispersible latex powder is selected from vinyl acetate-ethylene copolymer and vinyl acetate and ethylene copolymer rubber powder.

[0025] Furthermore, the redispersible latex powder includes redispersible latex powder of model 5010N, redispersible latex powder of model 5044N, and redispersible latex powder of model 5549H in a weight ratio of 1:(1.2-1.4):(0.6-0.8).

[0026] In the system of the present invention, by adding a specific type of redispersible latex, a synergistic effect is produced with modified basalt fiber, which can improve the waterproofness and lateral deformation ability of the waterproof mortar. At the same time, the shrinkage rate of the waterproof mortar can be improved. The redispersible latex and the modified basalt fiber form a composite reinforcement system in the mortar; the flexibility provided by the latex and the high strength provided by the fiber complement each other, so that the mortar has both good flexibility and high tensile strength; this composite reinforcement effect can significantly improve the comprehensive mechanical properties and waterproof properties of the mortar. The high tensile strength of the modified basalt fiber and the flexibility of the redispersible latex are combined, so that the mortar can maintain the integrity of the structure when subjected to lateral deformation, reducing the risk of cracking caused by deformation. In subway tunnel projects, waterproof mortars need to have excellent waterproof performance and anti-deformation ability to cope with complex geological conditions and dynamic loads. By adding a specific type of redispersible latex and modified basalt fiber, the comprehensive performance of the waterproof mortar can be significantly improved to ensure the safety and durability of the tunnel structure.

[0027] Furthermore, the cement is P.O42.5 ordinary Portland cement or P.O52.5 ordinary Portland cement.

[0028] Furthermore, the aggregate is one or more of quartz sand, calcium sand or river sand with a particle size of 30-100 mesh.

[0029] Furthermore, the defoamer is one or both of an organosilicon defoamer and a polyether defoamer.

[0030] Furthermore, the cellulose ether is one or both of methyl hydroxyethyl cellulose ether and methyl hydroxypropyl cellulose ether. The cellulose ether is characterized by being surface treated with glyoxal.

[0031] Furthermore, the water reducing agent is one or both of melamine and naphthalene sulfonate.

[0032] Furthermore, the water repellent is one or both of silicone water repellent powder and stearate.

[0033] The second aspect of the present invention provides a method for preparing the waterproof mortar containing modified basalt fiber, comprising the following steps: mixing the components of the waterproof mortar containing modified basalt fiber, stirring for 15-20 minutes, and obtaining the waterproof mortar containing modified basalt fiber.

[0034] The invention provides application of the waterproof mortar containing modified basalt fibers.

[0035] Furthermore, the waterproof mortar containing modified basalt fiber is used in waterproof engineering.

[0036] Furthermore, the waterproof mortar containing modified basalt fiber is used in waterproofing projects of subway tunnel projects.

[0037] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0038] 1. The present invention provides a waterproof mortar containing modified basalt fiber. The preparation method and operation conditions of the modified basalt fiber of the present invention are simple, the reaction time is short, and the washing is easy. The obtained product has good dispersibility, and synergistically acts with components such as redispersible latex, has good anti-cracking effect, high strength, and greatly improved waterproof effect. The waterproof mortar prepared by the present invention has excellent comprehensive performance and can be applied to waterproof projects such as subway tunnel projects.

[0039] 2. Adding the modified basalt fiber prepared by the above method to the waterproof mortar of the present invention can improve the bonding strength of the waterproof mortar under different conditions.

[0040] 3. In the system of the present invention, by adding a redispersible latex of a specific model and ratio, a synergistic effect is produced with the modified basalt fiber, which can improve the waterproofness and lateral deformation capacity of the waterproof mortar. DETAILED DESCRIPTION

[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] The raw materials used in the following examples of the present invention are all commercially available products:

[0043] Basalt fiber, purchased from Sichuan Fiberglass Group Co., Ltd., has a diameter of 12-16 μm and a length of 6-8 mm.

[0044] Quartz sand was purchased from Shuyu Industrial Co., Ltd., Jiangyou City, Sichuan Province.

[0045] Example 1

[0046] The present embodiment provides a waterproof mortar containing modified basalt fiber, comprising the following components in parts by weight: 37 parts of cement, 58.2 parts of aggregate, 1.6 parts of modified basalt fiber, 1.2 parts of redispersible latex powder, 0.13 parts of cellulose ether, 0.15 parts of defoaming agent, 0.16 parts of water reducing agent and 0.4 parts of calcium stearate.

[0047] The cement is P.O42.5 ordinary Portland cement.

[0048] The aggregate is quartz sand with a particle size of 30-100 meshes.

[0049] The defoamer is an organosilicon defoamer, produced by Mingling Chemical of Germany, model AGITAN 156.

[0050] The cellulose ether is methyl hydroxyethyl cellulose ether, produced by Gaomi Yinying New Materials Co., Ltd., model CR45000.

[0051] The water reducing agent is melamine water reducing agent, BASF (China) Co., Ltd., model F10.

[0052] The preparation method of the modified basalt fiber comprises the following steps: by weight:

[0053] (1) 5 parts of silane coupling agent KH550, 20 parts of polymer emulsion, 4 parts of silicone emulsion and 72 parts of water were mixed and stirred until uniform to obtain a modified liquid;

[0054] (2) adding basalt fiber to the modified liquid, with the weight ratio of basalt fiber to the modified liquid being 1:1.5; completely immersing for 1.5 hours to obtain a mixed material;

[0055] (3) The mixed material is placed in a suspension dryer, and then silicon dioxide is added. The average particle size of the silicon dioxide is 10 nm and the average specific surface area is 380 m 2 / g. Purchased from Jinlei Technology, model JL-SiO2-N10; the weight ratio of basalt fiber to silica is 3.6:1, dried to obtain modified basalt fiber.

[0056] The polymer emulsion includes styrene-acrylic emulsion, silicone-acrylic emulsion and pure acrylic emulsion in a weight ratio of 1:1.4:0.5. Styrene-acrylic emulsion is purchased from Badfu Group Co., Ltd., model RS300L. Silicone-acrylic emulsion is purchased from Shanghai Baolijia Chemical Co., Ltd., model BLJ-KD96. Pure acrylic emulsion is purchased from Badfu Group Co., Ltd., model RS2608.

[0057] The organosilicon emulsion is a silane emulsion purchased from Wacker Chemical (China) Co., Ltd., model BS1306.

[0058] The redispersible latex powder includes redispersible latex powder of model 5010N, redispersible latex powder of model 5044N and redispersible latex powder of model 5549H in a weight ratio of 1:1.3:0.7, all of which are purchased from Wacker Chemical (China) Co., Ltd.

[0059] The method for preparing the waterproof mortar containing modified basalt fiber comprises the following steps: mixing the components of the waterproof mortar containing modified basalt fiber, stirring for 20 minutes, and obtaining the waterproof mortar containing modified basalt fiber.

[0060] Example 2

[0061] The present embodiment provides a waterproof mortar containing modified basalt fiber, comprising the following components in parts by weight: 36 parts of cement, 60 parts of aggregate, 2 parts of modified basalt fiber, 1 part of redispersible latex powder, 0.2 parts of cellulose ether, 0.1 parts of defoaming agent, 0.2 parts of water reducing agent and 0.6 parts of calcium stearate.

[0062] The cement is P.O42.5 ordinary Portland cement.

[0063] The aggregate is quartz sand with a particle size of 30-100 meshes.

[0064] The defoamer is an organosilicon defoamer, produced by Mingling Chemical of Germany, model AGITAN 156.

[0065] The cellulose ether is methyl hydroxypropyl cellulose ether, Wuqiao Qiyuan Cellulose Co., Ltd., model G100000.

[0066] The water reducing agent is melamine, BASF (China) Co., Ltd., model F10.

[0067] The preparation method of the modified basalt fiber comprises the following steps: by weight:

[0068] (1) 8 parts of silane coupling agent KH550, 15 parts of polymer emulsion, 5 parts of silicone emulsion and 62 parts of water were mixed and stirred until uniform to obtain a modified liquid;

[0069] (2) adding basalt fiber into the modified liquid and soaking for 2 hours to obtain a mixed material; the weight ratio of basalt fiber to the modified liquid is 1:2;

[0070] (3) The mixed material is placed in a suspension dryer, and then silicon dioxide is added. The average particle size of the silicon dioxide is 10 nm and the average specific surface area is 380 m 2 / g. Purchased from Jinlei Technology, model JL-SiO2-N10; the weight ratio of basalt fiber to silica is 4:1, dried to obtain modified basalt fiber.

[0071] The polymer emulsion includes styrene-acrylic emulsion, silicone-acrylic emulsion and pure acrylic emulsion in a weight ratio of 1:1.3:0.6. Styrene-acrylic emulsion is purchased from Badfu Group Co., Ltd., model RS300L. Silicone-acrylic emulsion is purchased from Shanghai Baolijia Chemical Co., Ltd., model BLJ-KD96. Pure acrylic emulsion is purchased from Badfu Group Co., Ltd., model RS2608.

[0072] The organosilicon emulsion is a silane emulsion purchased from Wacker Chemical (China) Co., Ltd., model BS1306.

[0073] The redispersible latex powder includes redispersible latex powder of model 5010N, redispersible latex powder of model 5044N and redispersible latex powder of model 5549H in a weight ratio of 1:1.2:0.8, all of which are purchased from Wacker Chemical (China) Co., Ltd.

[0074] The method for preparing the waterproof mortar containing modified basalt fiber comprises the following steps: mixing the components of the waterproof mortar containing modified basalt fiber, stirring for 15 minutes, and obtaining the waterproof mortar containing modified basalt fiber.

[0075] Comparative Example 1

[0076] The difference between this comparative example and Example 1 is that no silicone emulsion is added in the preparation of the modified basalt fiber.

[0077] The preparation method of the modified basalt fiber comprises the following steps: by weight:

[0078] (1) 5 parts of silane coupling agent KH550, 20 parts of polymer emulsion and 72 parts of water were mixed and stirred until uniform to obtain a modified liquid;

[0079] (2) adding basalt fiber to the modified liquid, with the weight ratio of basalt fiber to the modified liquid being 1:1.5; completely immersing for 1.5 hours to obtain a mixed material;

[0080] (3) The mixed material is placed in a suspension dryer, and then silicon dioxide is added. The average particle size of the silicon dioxide is 10 nm and the average specific surface area is 380 m 2 / g. Purchased from Jinlei Technology, model JL-SiO2-N10; the weight ratio of basalt fiber to silica is 3.6:1, dried to obtain modified basalt fiber.

[0081] Comparative Example 2

[0082] The difference between this comparative example and Example 1 is that the silane coupling agent KH550 is not added in the preparation of the modified basalt fiber.

[0083] The preparation method of the modified basalt fiber comprises the following steps: by weight:

[0084] (1) 20 parts of polymer emulsion, 4 parts of silicone emulsion and 72 parts of water were mixed and stirred until uniform to obtain a modified liquid;

[0085] (2) adding basalt fiber to the modified liquid, with the weight ratio of basalt fiber to the modified liquid being 1:1.5; completely immersing for 1.5 hours to obtain a mixed material;

[0086] (3) The mixed material is placed in a suspension dryer, and then silicon dioxide is added. The average particle size of the silicon dioxide is 10 nm and the average specific surface area is 380 m 2 / g. Purchased from Jinlei Technology, model JL-SiO2-N10; the weight ratio of basalt fiber to silica is 3.6:1, dried to obtain modified basalt fiber.

[0087] Comparative Example 3

[0088] The difference between this comparative example and Example 1 is that the modified basalt fiber is kept the same, and the proportions of other components of the waterproof mortar are different.

[0089] A waterproof mortar containing modified basalt fiber comprises the following components in parts by weight: 42 parts of cement, 53.2 parts of aggregate, 1.6 parts of modified basalt fiber, 0.8 parts of redispersible latex powder, 0.08 parts of cellulose ether, 0.25 parts of defoamer, 0.11 parts of water reducing agent and 0.8 parts of calcium stearate.

[0090] Comparative Example 4

[0091] The difference between this comparative example and Example 1 is that the polymer emulsion includes styrene acrylic emulsion, silicone acrylic emulsion and pure acrylic emulsion in a weight ratio of 1:1:1.

[0092] Comparative Example 5

[0093] The difference between this comparative example and Example 1 is that the redispersible latex powder includes redispersible latex powder of model DA-1220, redispersible latex powder of model ATT-180 and redispersible latex powder of model CBYLT-8008 in a weight ratio of 1:1:1.

[0094] Comparative Example 6

[0095] The difference between this comparative example and Example 1 is that the added amount of modified basalt fiber is different.

[0096] A waterproof mortar containing modified basalt fiber comprises the following components in parts by weight: 37 parts of cement, 58.2 parts of aggregate, 0.6 parts of modified basalt fiber, 1.2 parts of redispersible latex powder, 0.13 parts of cellulose ether, 0.15 parts of defoamer, 0.16 parts of water reducing agent and 0.4 parts of calcium stearate.

[0097] Comparative Example 7

[0098] The difference between this comparative example and Example 1 is that no modified basalt fiber is added.

[0099] A waterproof mortar containing modified basalt fiber comprises the following components in parts by weight: 37 parts of cement, 59.8 parts of aggregate, 1.2 parts of redispersible latex powder, 0.13 parts of cellulose ether, 0.15 parts of defoamer, 0.16 parts of water reducing agent and 0.4 parts of calcium stearate.

[0100] Performance Testing

[0101] The waterproof mortar prepared in Examples 1-2 and Comparative Examples 1-7 was tested for performance according to JC / T984-2011 and freeze-thaw test according to JC / T547-2017.

[0102] The results are shown in Table 1.

[0103] Table 1 Test results of waterproof mortar

[0104]

[0105] It can be seen from Table 1 that the waterproof mortar prepared in Examples 1-2 has excellent comprehensive performance, which is mainly due to the synergistic compounding of the modified basalt prepared in the present invention and other multiple components.

[0106] However, the comparative examples were significantly inferior to the examples in the corresponding performance tests because they did not adopt the necessary technical solutions. In comparative example 1, no silicone emulsion was added to the modifying liquid, and in comparative example 2, no silane coupling agent was added to the modifying liquid. In comparative example 4, the polymer emulsion composition was different. It can be seen that the bonding strength of the waterproof mortar decreased, proving that the modifying liquid composition has an important influence on the bonding strength of the waterproof mortar. In comparative example 3, the modified basalt fiber was kept the same, and the proportions of other components of the waterproof mortar were different. From the results, it can be seen that the performance of the waterproof mortar decreased. , which shows the important influence of the proportion of waterproof mortar on the performance of waterproof mortar. In Example 5, the proportion of dispersible latex powder is different, and the impermeability of waterproof mortar decreases. In Example 6, the addition amounts of modified basalt fiber and redispersible latex powder are different, and the lateral deformation capacity of waterproof mortar decreases, which shows that there is a synergistic effect between the modified basalt fiber prepared by the present invention and the redispersible latex with a specific proportion. In Example 7, no modified basalt fiber is added, and the comprehensive performance of waterproof mortar decreases. The above experimental results further prove the importance of the technical scheme defined in the present invention for its technical effect.

[0107] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A waterproof mortar containing modified basalt fiber, characterized in that: The invention comprises the following components in parts by weight: 35-40 parts of cement, 55.3-62.4 parts of aggregate, 1-2 parts of modified basalt fiber, 1-1.5 parts of redispersible latex powder, 0.1-0.2 parts of cellulose ether, 0.1-0.2 parts of defoaming agent, 0.1-0.2 parts of water reducing agent and 0.3-0.6 parts of water repellent; The preparation method of the modified basalt fiber comprises the following steps: by weight: (1) mixing 3-8 parts of a coupling agent, 15-25 parts of a polymer emulsion, 3-5 parts of an organosilicon emulsion and 62-79 parts of water, and stirring until uniform to obtain a modified liquid; (2) adding basalt fiber into the modified liquid and soaking for 1-2 hours to obtain a mixed material; (3) The mixed material is placed in a suspension dryer, and then silicon dioxide is added and dried to obtain modified basalt fiber.

2. The waterproof mortar containing modified basalt fiber according to claim 1, characterized in that: In the step (2), the weight ratio of basalt fiber to modifying liquid is 1:(1-2).

3. The waterproof mortar containing modified basalt fiber according to claim 1, characterized in that: The weight ratio of basalt fiber to silicon dioxide in the step (3) is (3-4):

1.

4. The waterproof mortar containing modified basalt fiber according to claim 1, characterized in that: In the step (1), the polymer emulsion is selected from one or more of pure acrylic emulsion, styrene acrylic emulsion, acetic acid acrylic emulsion, silicone acrylic emulsion and chloroacrylic emulsion.

5. The waterproof mortar containing modified basalt fiber according to claim 4, characterized in that: The polymer emulsion comprises styrene-acrylic emulsion, silicone-acrylic emulsion and pure acrylic emulsion in a weight ratio of 1:(1.3-1.5):(0.4-0.6).

6. The waterproof mortar containing modified basalt fiber according to claim 1, characterized in that: The organosilicon emulsion is one or both of silane emulsion and siloxane emulsion.

7. The waterproof mortar containing modified basalt fiber according to claim 1, characterized in that: The redispersible latex powder includes redispersible latex powder of model 5010N, redispersible latex powder of model 5044N and redispersible latex powder of model 5549H in a weight ratio of 1:(1.2-1.4):(0.6-0.8).

8. The waterproof mortar containing modified basalt fiber according to claim 1, characterized in that: The cellulose ether is one or both of methyl hydroxyethyl cellulose ether and methyl hydroxypropyl cellulose ether.

9. A method for preparing a waterproof mortar containing modified basalt fiber according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing components of the waterproof mortar containing modified basalt fiber, and stirring for 15-20 minutes to obtain the waterproof mortar containing modified basalt fiber.

10. Use of the waterproof mortar containing modified basalt fiber according to any one of claims 1 to 8 in waterproof engineering.

Citation Information

Cited By

  • Modified basalt fiber reinforced self-leveling mortar and preparation method thereof

    CN122325192A